Why philosophize? - Lyotard, Jean-Francois 192-1998 (Polity Press, 2013)
"Why Philosophize? is a series of lectures given by Jean-Francois Lyotard to students at the Sorbonne embarking on their university studies. The circumstances obliged him to be both clear and concise: at the same time, his lectures offer a profound and far-reaching meditation on how essential it is to philosophize in a world where philosophy often seems irrelevant, outdated, or inconclusive. Lyotard begins by drawing on Plato, Proust and Lacan to show that philosophy is a never-ending desire--for wisdom, for the 'other'. In the second lecture he draws on Heraclitus and Hegel to explore the close relation between philosophy and history: the same restlessness, the same longing for a precarious unity, drives both. In his third lecture, Lyotard examines how philosophy is a form of speech that plays on the borders of what can be communicated directly. Finally, he turns to Marx, exploring the extent to which philosophy can be a transformative force within the world. These wonderfully accessible lectures will attract a wide readership, since, as Lyotard says, 'How can one not philosophize?' They are also an excellent introduction to Lyotard's thought."--Page 4 of cover.